A Fast and Adaptive Dynamic Phasor Estimation Algorithm Implemented on Field Programmable Gate Array (FPGA) - Samantaray, Subhransu Ranjan; Nanda, Sarita; Dash, P.K. (IEEE transactions on industrial electronics (1982), 2022)
A fast and precise dynamic phasor estimation algorithm using an adaptive improved second order Levenberg-Marquadt algorithm under stressed and off-nominal frequency circumstances is proposed in this paper. The proposed algorithm ventures a faster quasi-second-order method and in addition, the learning rate is also made adaptive to speed up the convergence. Moreover, the projected estimator essentially filters harmonics, estimates transients in a signal during faults and effectually performs in complex modulated setting which is found commonly in a power system with distributed energy resources. Outcomes reveal that the estimation errors and the convergence time of the proposed approach is way below the minimum requirement of the IEEE C37.118.1 standard. Besides, due to its reduced complexity, the estimator has been successfully implemented on the field programmable gate array (FPGA) platform and has been verified on a practical microgrid scenario including photo voltaic systems. The performance during testing indicates that the proposed technique has potential ability to perform under stressed conditions conforming the accuracy and speed of response.